Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Ocean circulation, sea ice, and productivity simulated in Jones Sound, Canadian Arctic Archipelago, between 2003–2016 - Tyler Pelle; Paul G. Myers; Andrew Hamilton; Matthew Mazloff; Krista M. Soderlund; Lucas Beem; Donald D. Blankenship; Cyril Grima; Feras Habbal; Mark Skidmore; Jamin S. Greenbaum (Ocean Science, 2026)
Jones Sound is one of three critical waterways in the Canadian Arctic Archipelago that regulate liquid exchange between the Arctic Ocean and northern Atlantic Ocean. However, to date, no high-resolution ocean circulation model exists to study the recent evolution of Jones Sound, meaning that our understanding of circulation within the sound is based either on temporally and spatially sparse oceanographic observations or on extrapolating conditions within Baffin Bay, which has a more dense observational record. To address this, we develop a high-resolution (1/120°, 0.9 km) Jones Sound configuration of the Massachusetts Institute of Technology general circulation model and perform coupled ocean–sea ice–biological productivity simulations between 2003–2016. We find that circulation through Lady Ann Strait, Fram Sound, and Glacier Strait comprises 71 %, 14 %, and 15 % of the volumetric transport into and out of Jones Sound, with tidal flushing enhancing the magnitude of volumetric transport through Fram Sound. Warming Atlantic Water within western Baffin Bay flows into Jones Sound through Lady Ann Strait, becomes well-mixed, and circulates counterclockwise, encroaching on the terminus of most tidewater glaciers that line the eastern periphery of the sound. Furthermore, we find that sustained atmospheric and oceanic warming drives an 11 % reduction in the 2003–2016 mean summertime sea ice area, decreased wintertime sea ice thickness, and delayed onset of sea ice refreeze in the fall (thus lengthening the amount of time during which Jones Sound is ice-free). Tidal flushing through Cardigan Strait is critical in triggering melt-back of sea ice across northern Jones Sound. Lastly, this decline in sea ice increases light availability and, when coupled with warming of the subsurface waters in Jones Sound, facilitates enhanced primary productivity down to ∼ 21 m depth. While we note that the modeled warming signal in Baffin Bay is overestimated relative to observations, the results presented here improve our general understanding of how this critical waterway might change under continued polar-amplified global warming and underscores the need for sustained oceanographic observations in this region.

Comparing impacts and recovery of locally managed reefs after exposure to extreme waves from a category 5 cyclone - Amanda K. Ford; Mark Hamilton; Yashika Nand; Marji Puotinen; Stacy D. Jupiter; Sirilo Dulunaqio; Waisea Naisilisili; Sangeeta Mangubhai (Coral Reefs, 2025)
As the climate warms, coral reefs face more frequent and severe impacts from thermal stress while a greater proportion of tropical cyclones are expected to reach the strongest categories. Understanding the impacts of extreme cyclone waves and reef recovery dynamics is essential to support projections of reef communities under future climate scenarios. We present an evaluation of 18 sites across two large barrier reef systems in Fiji under varying forms of local management using data collected prior, directly after, and four years following Tropical Cyclone Winston (2016), which generated extreme waves 11 standard deviations above the long-term average. Our study aimed to: (1) determine how storm wave energy links to changes in hard coral cover; (2) quantify the impact and recovery of benthic communities on reefs with different management interventions; and (3) assess fish community trajectories in relation to observed differences in benthic communities and/or management. The cyclone’s impact on benthic communities was severe, with a relative loss of 54 ± 8% hard coral cover (primarily branching and plating Acropora ) and corresponding increases in rubble and turf algae. However, hard coral recovery and reassembly by 2020 was rapid and extensive, indicating high resilience. Fish biomass was consistently high with variable effects of no-take areas, and functional groups were minimally impacted by the cyclone. No-take areas did not promote faster recovery, but all sites were removed from local impacts, known to be highly productive and exposed to strong currents that are expected to facilitate high resilience. Identifying and prioritising resilient sites for management is crucial for the future of coral reefs.

Perturbation solution for second-harmonic generation in focused shear wave beams in soft solids - Philip G. Kaufinger; John M. Cormack; Kyle S. Spratt; Mark F. Hamilton (Wave Motion, 2025)

A quantitative microbial risk assessment (QMRA) approach to determine water quality guidelines for Mycobacterium avium complex (MAC) in building plumbing - Sayalee Joshi; Hunter Quon; Yun Shen; Lutgarde Raskin; Mark H. Weir; Rajveer Singh; Patrick L. Gurian; Kerry A. Hamilton (Water Research, 2025)

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

In vivo labeling reveals that degranulation is increased under supraphysiological TCR stimulation, but not infection, in CD8+ T cells from old mice - Korbyn J. V. Dahlquist; Emma M. Dehm; Declan M. Smith; Erin D. Lucas; Mark Pierson; Sara E. Hamilton; Christina D. Camell (GeroScience, 2025)
CD8 + T cells exhibit distinct changes with aging, including a diminished naïve cell pool, an expansion of memory and exhausted cells, and altered effector molecule production, altogether leading to increased susceptibility to infection. They have reduced cytotoxicity in vivo, but increased granule content and faster cytotoxic kinetics to target cells in vitro . Whether CD8 + T cells from old mice degranulate when activated in vivo , within the aged environment, is unknown. This study investigates in vitro and in vivo degranulation of CD8 + T cells from young and old mice during supraphysiological aCD3 stimulation and two types of infection. Actively degranulating CD8 + CD44 + T cells were identified by positive labeling after a two-hour exposure to granule-specific fluorescent antibodies (CD107a and CD107b). Surprisingly, CD8 + T cells from old mice challenged with supraphysiological TCR-specific stimulation exhibited higher levels of degranulation as compared to their young counterparts. This effect is more prominent in vitro and can be partially explained by the age-specific increase in CD8 + CD44 + CD62L − cells. However, during microbial exposure or LCMV Armstrong infection, we show that CD8 + CD44 + and antigen-specific T cells from old mice have reduced degranulation, consistent with the diminished cytotoxic capacity. These data highlight the preserved intrinsic cytotoxic capacity of memory CD8 + T cells from old mice and suggest that the aged microenvironment and type of stimulation are contributing factors to the lower degranulation and cytotoxic capacity of these cells. This provides insight into the potential of increasing T cell activation to improve vaccine approaches in the elderly.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The impact of beauvericin on rainbow trout intestinal epithelial cells at different temperatures and dosing methods - Vivian R. Dayeh; Anita Solhaug; Mark E. Hamilton; Laura E. Linton; Lucy E. J. Lee; Niels C. Bols (In Vitro Cellular & Developmental Biology - Animal, 2025)

A Comprehensive Review on Utilizing Human Brain Organoids to Study Neuroinflammation in Neurological Disorders - Adrian Domene Rubio; Luke Hamilton; Mark Bausch; Mengmeng Jin; Ava Papetti; Peng Jiang; Sowmya V. Yelamanchili (Journal of Neuroimmune Pharmacology, 2025)

Ultraviolet absorbents and industrial antioxidants in seabirds, mammals, and fish from the Canadian Arctic - Ingrid-Alejandra Granados-Galvan; Jennifer F. Provencher; Mark L. Mallory; Amila De Silva; Derek C.G. Muir; Jane L. Kirk; Xiaowa Wang; Robert J. Letcher; Lisa L. Loseto; Bonnie M. Hamilton; Zhe Lu (Science of The Total Environment, 2024)

Examining ingested microplastics in fish: Considerations on filter pore size, analysis time, and material costs to design cost-effective projects - Caitlin Brawn; Bonnie M. Hamilton; Matthew S. Savoca; Mark L. Mallory; Jennifer F. Provencher (Marine Environmental Research, 2024)

Retraction Note: MDMA-assisted psychotherapy for treatment of PTSD: study design and rationale for phase 3 trials based on pooled analysis of six phase 2 randomized controlled trials - Michael C. Mithoefer; Allison A. Feduccia; Lisa Jerome; Anne Mithoefer; Mark Wagner; Zach Walsh; Scott Hamilton; Berra Yazar-Klosinski; Amy Emerson; Rick Doblin (Psychopharmacology, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Durability of the moderate-to-heavy-intensity transition is related to the effects of prolonged exercise on severe-intensity performance - Kate Hamilton; Andrew E. Kilding; Daniel J. Plews; Mathew J. Mildenhall; Mark Waldron; Thanchanok Charoensap; Tobias H. Cox; Matthew J. Brick; Warren B. Leigh; Ed Maunder (European Journal of Applied Physiology, 2024)
Purpose Power output at the moderate-to-heavy-intensity transition decreases during prolonged exercise, and resilience to this has been termed ‘durability’. The purpose of this study was to assess the relationship between durability and the effect of prolonged exercise on severe-intensity performance, and explore intramuscular correlates of durability. Methods On separate days, 13 well-trained cyclists and triathletes (V̇O 2 peak, 57.3 ± 4.8 mL kg −1 min −1 ; training volume, 12 ± 2.1 h week −1 ) undertook an incremental test and 5-min time trial (TT) to determine power output at the first ventilatory threshold (VT 1 ) and severe-intensity performance, with and without 150-min of prior moderate-intensity cycling. A single resting vastus lateralis microbiopsy was obtained. Results Prolonged exercise reduced power output at VT 1 (211 ± 40 vs. 198 ± 39 W, ∆ -13 ± 16 W, ∆ -6 ± 7%, P = 0.013) and 5-min TT performance (333 ± 75 vs. 302 ± 63 W, ∆ -31 ± 41 W, ∆ -9 ± 10%, P = 0.017). The reduction in 5-min TT performance was significantly associated with durability of VT 1 (r s = 0.719, P = 0.007). Durability of VT 1 was not related to vastus lateralis carnosine content, citrate synthase activity, or complex I activity ( P > 0.05). Conclusion These data provide the first direct support that durability of the moderate-to-heavy-intensity transition is an important performance parameter, as more durable athletes exhibited smaller reductions in 5-min TT performance following prolonged exercise. We did not find relationships between durability and vastus lateralis carnosine content, citrate synthase activity, or complex I activity.

Traversing the land‐sea interface: A climate change risk assessment of terrestrially breeding marine predators - Milan Sojitra; Stuart Corney; Mark Hemer; Sheryl Hamilton; Julie McInnes; Sam Thalmann; Mary‐Anne Lea (Global Change Biology, 2024)
Terrestrially breeding marine predators have experienced shifts in species distribution, prey availability, breeding phenology, and population dynamics due to climate change worldwide. These central‐place foragers are restricted within proximity of their breeding colonies during the breeding season, making them highly susceptible to any changes in both marine and terrestrial environments. While ecologists have developed risk assessments to evaluate climate risk in various contexts, these often overlook critical breeding biology data. To address this knowledge gap, we developed a trait‐based risk assessment framework, focusing on the breeding season and applying it to marine predators breeding in parts of Australian territory and Antarctica. Our objectives were to quantify climate change risk, identify specific threats, and establish an adaptable assessment framework. The assessment considered 25 criteria related to three risk components: vulnerability, exposure, and hazard, while accounting for uncertainty. We employed a scoring system that integrated a systematic literature review and expert elicitation for the hazard criteria. Monte Carlo sensitivity analysis was conducted to identify key factors contributing to overall risk. We identified shy albatross ( Thalassarche cauta ), southern rockhopper penguins ( Eudyptes chrysocome ), Australian fur seals ( Arctocephalus pusillus doriferus ), and Australian sea lions ( Neophoca cinerea ) with high climate urgency. Species breeding in lower latitudes, as well as certain eared seal, albatross, and penguin species, were particularly at risk. Hazard and exposure explained the most variation in relative risk, outweighing vulnerability. Key climate hazards affecting most species include extreme weather events, changes in habitat suitability, and prey availability. We emphasise the need for further research, focusing on at‐risk species, and filling knowledge gaps (less‐studied hazards, and/or species) to provide a more accurate and robust climate change risk assessment. Our findings offer valuable insights for conservation efforts, given that monitoring and implementing climate adaptation strategies for land‐dependent marine predators is more feasible during their breeding season.

Variations in antimicrobial resistance genes present in the rectal faeces of seals in Scottish and Liverpool Bay coastal waters - Eleanor Watson; Scott Hamilton; Nuno Silva; Simon Moss; Craig Watkins; Johanna Baily; Thorsten Forster; Ailsa J. Hall; Mark P. Dagleish (Environmental Pollution, 2024)

Bitou bush detection and mapping using UAV-based multispectral and hyperspectral imagery and artificial intelligence - Narmilan Amarasingam; Jane E Kelly; Juan Sandino; Mark Hamilton; Felipe Gonzalez; Remy L Dehaan; Lihong Zheng; Hillary Cherry (Remote Sensing Applications: Society and Environment, 2024)

Shorebird Abundance is Associated with Nutritional Quality of Intertidal Biofilm on the Fraser River Estuary - Mark C. Drever; Matthew J. Mogle; Tristan J. Douglas; Scott A. Flemming; Diana J. Hamilton; Justin D. Liefer; Robert W. Elner (Estuaries and Coasts, 2024)
Dense congregations of shorebirds forage on tidal flats during long-distance migration, and their abundance is presumed to mirror the underlying ecological conditions. We quantified the nutritional content of intertidal biofilm (a thin layer of microalgae, bacteria, and other microorganisms embedded in a mucilaginous matrix that sits on the surface of tidal flats) to assess whether biofilm biomass, macronutrient content (lipid, protein, and carbohydrate), or both, provide a measure of habitat quality for migrating shorebirds. We compared shorebird use, biofilm biomass, macronutrient content, and stable isotope signatures at two mudflats on the Fraser River estuary, British Columbia, Canada, during summer 2020 (southward migration) and spring 2021 (northward migration). The abundances of Western Sandpiper ( Calidris mauri ) and Dunlin ( Calidris alpina ) were consistently higher (6–100×) at Brunswick Point relative to the Iona Foreshore site during both migration periods. Biofilm biomass (chlorophyll a ) was 2× higher at Brunswick Point than Iona Foreshore during southward migration, and was similar between sites during northward migration, suggesting biofilm biomass alone was not a main determinant of shorebird use of these sites. Macronutrient content (lipid, protein, and carbohydrate) in intertidal biofilm was 1.4× to 3.8× higher at Brunswick Point than Iona Foreshore during both migration periods, indicating an association between macronutrient content and shorebird use. Carbohydrate content was higher during southward migration at both tidal flats, whereas protein and lipid content at Iona Foreshore did not show significant differences between years or migration periods. Carbon and nitrogen stable isotope signatures during spring 2021 did not differ between the two sites, suggesting that nutrients had similar relative inputs from marine and freshwater sources. While our comparative study does not eliminate alternative explanations that might act concomitantly (e.g., invertebrate abundance, predation risk, and disturbance), our results are consistent with the hypothesis that small-bodied shorebirds are more abundant at sites where intertidal biofilm has high macronutrient content. The latter can vary in complex ways depending on the taxonomic composition and physiological state of the microphytobenthos. Thus, the nutritional “quality” of intertidal biofilm can serve as a useful measure for determining restoration goals for tidal flats or assessing coastal areas for development projects.

Predictive geochemical mapping using machine learning in western Kenya - Olivier S. Humphrey; Mark Cave; Elliott M. Hamilton; Odipo Osano; Diana Menya; Michael J. Watts (Geoderma Regional, 2023)

A marine protected area network does not confer community structure resilience to a marine heatwave across coastal ecosystems - Joshua G. Smith; Christopher M. Free; Cori Lopazanski; Julien Brun; Clarissa R. Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; Scott L. Hamilton; David Mouillot; et al. (Global Change Biology, 2023)
Marine protected areas (MPAs) have gained attention as a conservation tool for enhancing ecosystem resilience to climate change. However, empirical evidence explicitly linking MPAs to enhanced ecological resilience is limited and mixed. To better understand whether MPAs can buffer climate impacts, we tested the resistance and recovery of marine communities to the 2014–2016 Northeast Pacific heatwave in the largest scientifically designed MPA network in the world off the coast of California, United States. The network consists of 124 MPAs (48 no‐take state marine reserves, and 76 partial‐take or special regulation conservation areas) implemented at different times, with full implementation completed in 2012. We compared fish, benthic invertebrate, and macroalgal community structure inside and outside of 13 no‐take MPAs across rocky intertidal, kelp forest, shallow reef, and deep reef nearshore habitats in California's Central Coast region from 2007 to 2020. We also explored whether MPA features, including age, size, depth, proportion rock, historic fishing pressure, habitat diversity and richness, connectivity, and fish biomass response ratios (proxy for ecological performance), conferred climate resilience for kelp forest and rocky intertidal habitats spanning 28 MPAs across the full network. Ecological communities dramatically shifted due to the marine heatwave across all four nearshore habitats, and MPAs did not facilitate habitat‐wide resistance or recovery. Only in protected rocky intertidal habitats did community structure significantly resist marine heatwave impacts. Community shifts were associated with a pronounced decline in the relative proportion of cold water species and an increase in warm water species. MPA features did not explain resistance or recovery to the marine heatwave. Collectively, our findings suggest that MPAs have limited ability to mitigate the impacts of marine heatwaves on community structure. Given that mechanisms of resilience to climate perturbations are complex, there is a clear need to expand assessments of ecosystem‐wide consequences resulting from acute climate‐driven perturbations, and the potential role of regulatory protection in mitigating community structure changes.

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Planktic foraminifera iodine/calcium ratios from plankton tows - Helge A. Winkelbauer; Babette A. A. Hoogakker; Rosie J. Chance; Catherine V. Davis; Christopher J. Anthony; Juliane Bischoff; Lucy J. Carpenter; Simon R. N. Chenery; Elliott M. Hamilton; Philip Holdship; Victoria L. Peck; Alex J. Poulton; et al. (Frontiers in Marine Science, 2023)
Planktic foraminifera test iodine to calcium ratios represent an emerging proxy method to assess subsurface seawater oxygenation states. Several core-top studies show lower planktic foraminifera I/Ca in locations with oxygen depleted subsurface waters compared to well oxygenated environments. The reasoning behind this trend is that only the oxidized species of iodine, iodate, is incorporated in foraminiferal calcite. The I/Ca of foraminiferal calcite is thought to reflect iodate contents in seawater. To test this hypothesis, we compare planktic foraminifera I/Ca ratios, obtained from plankton tows, with published and new seawater iodate concentrations from 1) the Eastern North Pacific with extensive oxygen depletion, 2) the Benguela Current System with moderately depleted oxygen concentrations, and 3) the well oxygenated North and South Atlantic. We find the lowest I/Ca ratios (0.07 µmol/mol) in planktic foraminifera retrieved from the Eastern North Pacific, and higher values for samples (up to 0.72 µmol/mol) obtained from the Benguela Current System and North and South Atlantic. The I/Ca ratios of plankton tow foraminifera from environments with well oxygenated subsurface waters, however, are an order of magnitude lower compared to core-tops from similarly well-oxygenated regions. This would suggest that planktic foraminifera gain iodine post-mortem, either when sinking through the water column, or during burial.

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Climate impacts alter fisheries productivity and turnover on coral reefs - Mark Hamilton; James P. W. Robinson; Cassandra E. Benkwitt; Shaun K. Wilson; M. Aaron MacNeil; Ameer Ebrahim; Nicholas A. J. Graham (Coral Reefs, 2022)
Alteration of benthic reef habitat after coral bleaching and mortality induces changes in fish assemblages, with implications for fisheries. Our understanding of climate impacts to coral reef fisheries is largely based on fish abundance and biomass. The rates at which biomass is produced and replenished (productivity and turnover) are also important to sustaining fisheries, yet the responses of these metrics following bleaching are largely unknown. Here, we examine changes in fish productivity and turnover after mass coral bleaching events in Seychelles, on reefs that were recovering to coral-dominated habitats and those that shifted to macroalgae-dominated regimes. Productivity of fish assemblages increased on all recovering reefs, particularly on fished reefs resulting in levels similar to protected reefs 19 years after bleaching. Herbivore-detritivores, such as scraping and excavating parrotfish, appeared to drive biomass production through increased abundance on recovering reefs. Productivity on regime-shifted reefs remained stable at 1994 levels in fished areas, with increases observed on protected reefs. Large increases in browser productivity (particularly on protected reefs), combined with increases for invertivores, maintained post-bleaching productivity on macroalgal reefs. For all diet groups, net turnover was generally higher on fished regime-shifted reefs than on recovering reefs, suggesting fish biomass is more readily replenished on macroalgal reefs. Reef structural complexity was a positive predictor of productivity for all diet groups. These findings indicate that post-bleaching reef fish productivity is strongly influenced by benthic recovery trajectories, and demonstrates the importance of herbivore and invertivore species in sustaining small-scale inshore fisheries following climatic disturbances.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Geographic variation in responses of kelp forest communities of the California Current to recent climatic changes - Rodrigo Beas‐Luna; Fiorenza Micheli; C. Brock Woodson; Mark Carr; Dan Malone; Jorge Torre; Charles Boch; Jennifer E. Caselle; Matt Edwards; Jan Freiwald; Scott L. Hamilton; Arturo Hernandez; et al. (Global Change Biology, 2020)
The changing global climate is having profound effects on coastal marine ecosystems around the world. Structure, functioning, and resilience, however, can vary geographically, depending on species composition, local oceanographic forcing, and other pressures from human activities and use. Understanding ecological responses to environmental change and predicting changes in the structure and functioning of whole ecosystems require large‐scale, long‐term studies, yet most studies trade spatial extent for temporal duration. We address this shortfall by integrating multiple long‐term kelp forest monitoring datasets to evaluate biogeographic patterns and rates of change of key functional groups (FG) along the west coast of North America. Analysis of data from 469 sites spanning Alaska, USA, to Baja California, Mexico, and 373 species (assigned to 18 FG) reveals regional variation in responses to both long‐term (2006–2016) change and a recent marine heatwave (2014–2016) associated with two atmospheric and oceanographic anomalies, the “Blob” and extreme El Niño Southern Oscillation (ENSO). Canopy‐forming kelps appeared most sensitive to warming throughout their range. Other FGs varied in their responses among trophic levels, ecoregions, and in their sensitivity to heatwaves. Changes in community structure were most evident within the southern and northern California ecoregions, while communities in the center of the range were more resilient. We report a poleward shift in abundance of some key FGs. These results reveal major, ongoing region‐wide changes in productive coastal marine ecosystems in response to large‐scale climate variability, and the potential loss of foundation species. In particular, our results suggest that coastal communities that are dependent on kelp forests will be more impacted in the southern portion of the California Current region, highlighting the urgency of implementing adaptive strategies to sustain livelihoods and ensure food security. The results also highlight the value of multiregional integration and coordination of monitoring programs for improving our understanding of marine ecosystems, with the goal of informing policy and resource management in the future.

Comparative landscape genetics reveals differential effects of environment on host and pathogen genetic structure in Tasmanian devils ( Sarcophilus harrisii ) and their transmissible tumour - Christopher P. Kozakiewicz; Lauren Ricci; Austin H. Patton; Amanda R. Stahlke; Sarah A. Hendricks; Mark J. Margres; Manuel Ruiz‐Aravena; David G. Hamilton; Rodrigo Hamede; Hamish McCallum; Menna E. Jones; Paul A. Hohenlohe; et al. (Molecular Ecology, 2020)
Genetic structure in host species is often used to predict disease spread. However, host and pathogen genetic variation may be incongruent. Understanding landscape factors that have either concordant or divergent influence on host and pathogen genetic structure is crucial for wildlife disease management. Devil facial tumour disease (DFTD) was first observed in 1996 and has spread throughout almost the entire Tasmanian devil geographic range, causing dramatic population declines. Whereas DFTD is predominantly spread via biting among adults, devils typically disperse as juveniles, which experience low DFTD prevalence. Thus, we predicted little association between devil and tumour population structure and that environmental factors influencing gene flow differ between devils and tumours. We employed a comparative landscape genetics framework to test the influence of environmental factors on patterns of isolation by resistance (IBR) and isolation by environment (IBE) in devils and DFTD. Although we found evidence for broad‐scale costructuring between devils and tumours, we found no relationship between host and tumour individual genetic distances. Further, the factors driving the spatial distribution of genetic variation differed for each. Devils exhibited a strong IBR pattern driven by major roads, with no evidence of IBE. By contrast, tumours showed little evidence for IBR and a weak IBE pattern with respect to elevation in one of two tumour clusters we identify herein. Our results warrant caution when inferring pathogen spread using host population genetic structure and suggest that reliance on environmental barriers to host connectivity may be ineffective for managing the spread of wildlife diseases. Our findings demonstrate the utility of comparative landscape genetics for identifying differential factors driving host dispersal and pathogen transmission.

Development and field assessment of transgenic hybrid switchgrass for improved biofuel traits - Lisa Alexander; Catherine Hatcher; Mitra Mazarei; Ellen Haynes; Holly Baxter; Keonhee Kim; Choo Hamilton; Robert Sykes; Geoffrey Turner; Mark Davis; Zeng-Yu Wang; Nicole Labbé; et al. (Euphytica, 2020)

RETRACTED ARTICLE: MDMA-assisted psychotherapy for treatment of PTSD: study design and rationale for phase 3 trials based on pooled analysis of six phase 2 randomized controlled trials - Michael C. Mithoefer; Allison A. Feduccia; Lisa Jerome; Anne Mithoefer; Mark Wagner; Zach Walsh; Scott Hamilton; Berra Yazar-Klosinski; Amy Emerson; Rick Doblin (Psychopharmacology, 2019)
Background Posttraumatic stress disorder is a prevalent mental health condition with substantial impact on daily functioning that lacks sufficient treatment options. Here we evaluate six phase 2 trials in a pooled analysis to determine the study design for phase 3 trials of MDMA-assisted psychotherapy for PTSD. Methods Six randomized, double-blind, controlled clinical trials at five study sites were conducted from April 2004 to February 2017. Active doses of MDMA (75–125 mg, n = 72) or placebo/control doses (0–40 mg, n = 31) were administered to individuals with PTSD during manualized psychotherapy sessions in two or three 8-h sessions spaced a month apart. Three non-drug 90-min therapy sessions preceded the first MDMA exposure, and three to four followed each experimental session. Results After two blinded experimental sessions, the active group had significantly greater reductions in CAPS-IV total scores from baseline than the control group [MMRM estimated mean difference (SE) between groups − 22.0 (5.17), P < 0.001]. The between-group Cohen’s d effect size was 0.8, indicating a large treatment effect. After two experimental sessions, more participants in the active group (54.2%) did not meet CAPS-IV PTSD diagnostic criteria than the control group (22.6%). Depression symptom improvement on the BDI-II was greatest for the active group compared to the control group, although only trended towards significant group differences [MMRM, estimated mean difference (SE) between groups − 6.0 (3.03), P = 0.053]. All doses of MDMA were well tolerated, with some expected reactions occurring at greater frequency for the active MDMA group during experimental sessions and the 7 days following. Conclusions MDMA-assisted psychotherapy was efficacious and well tolerated in a large sample of adults with PTSD. These studies supported expansion into phase 3 trials and led to FDA granting Breakthrough Therapy designation for this promising treatment. Trial registration ClinicalTrials.gov Identifier: NCT00090064, NCT00353938, NCT01958593, NCT01211405, NCT01689740, NCT01793610.

Climate change adaptation, social capital, and the performance of polycentric governance institutions - Matthew L. Hamilton; Mark Lubell (Climatic Change, 2019)

Heparin impairs angiogenic signaling and compensatory lung growth after left pneumonectomy - Duy T. Dao; Lorenzo Anez-Bustillos; Jared Ourieff; Amy Pan; Paul D. Mitchell; Hiroko Kishikawa; Gillian L. Fell; Meredith A. Baker; Randolph S. Watnick; Hong Chen; Thomas E. Hamilton; Michael S. Rogers; et al. (Angiogenesis, 2018)

From Gondwana to GAAR landia: Evolutionary history and biogeography of ogre‐faced spiders ( Deinopis ) - Lisa Chamberland; Anne McHugh; Sarah Kechejian; Greta J. Binford; Jason E. Bond; Jonathan Coddington; Gaynor Dolman; Chris A. Hamilton; Mark S. Harvey; Matjaž Kuntner; Ingi Agnarsson (Journal of Biogeography, 2018)
Aim We explore the evolutionary history of the ogre‐faced spiders ( Deinopis ) from their Early Cretaceous origins to present day. Specifically, we investigate how vicariance and dispersal have shaped distribution patterns of this lineage. Within the Caribbean, we test the role of GAAR landia, a hypothesized land bridge that connected South America to the Greater Antilles during the Eocene–Oligocene transition (~35–33 Ma), in the biogeography of Deinopis . Taxon Araneae: Deinopidae: Deinopis . Location Caribbean islands, with additional global exemplars. Methods Combining standard Sanger sequence data with an Anchored Hybrid Enrichment ( AHE ) phylogenomic dataset, we use Bayesian inference to estimate the phylogenetic relationships of Deinopis . “BioGeo BEARS ” is used to test the GAAR landia hypothesis, and to pinpoint major dispersal events in the biogeographic history of Deinopis . Results The phylogeny supports the nesting of a Caribbean clade within a continental grade. Model comparisons indicate GAAR landia as the best fitting model, and the biogeographic analyses reflect the geologic history within the Caribbean. Ancient and recent overwater dispersal events are also indicated within this lineage. There is also an ancient 113 Ma split into Old and New World clades. Main Conclusions The Deinopis phylogeny corresponds well with geography. This is reflected in the support for the GAAR landia land bridge hypothesis and the phylogenetic relationships within and among Caribbean islands mirroring nuances of Caribbean geologic history. Overwater dispersal also plays an important role in the biogeographic history of this lineage as implicated in the colonization of the volcanic and sedimentary Lesser Antilles and in a “reverse” colonization of North America. The spider family Deinopidae is an ancient lineage with origins dating back to Gondwana. While overwater dispersal has clearly played a role in the biogeography of the genus, the Deinopis phylogeny bears a strong signature of ancient geological events.

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

From the forests to teeth: Visual crossdating to refine age estimates in marine mammals - Vicki Hamilton; Karen Evans; Mark A. Hindell (Marine Mammal Science, 2017)

Wildfire, climate, and perceptions in Northeast Oregon - Lawrence C. Hamilton; Joel Hartter; Barry D. Keim; Angela E. Boag; Michael W. Palace; Forrest R. Stevens; Mark J. Ducey (Regional Environmental Change, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Reduction of Ethanol Yield from Switchgrass Infected with Rust Caused by Puccinia emaculata - Virginia R. Sykes; Fred L. Allen; Jonathan R. Mielenz; C. Neal Stewart; Mark T. Windham; Choo Y. Hamilton; Miguel Rodriguez; Kelsey L. Yee (BioEnergy Research, 2016)

Isolation and characterization of 29 microsatellite markers for the bumphead parrotfish, Bolbometopon muricatum, and cross amplification in 12 related species - Mark A. Priest; Glenn R. Almany; Camrin D. Braun; Richard J. Hamilton; Diego F. Lozano-Cortés; Pablo Saenz-Agudelo; Michael L. Berumen (Marine Biodiversity, 2015)

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

Characterization of a thermophilic bacteriophage of Geobacillus kaustophilus - Timothy J. Marks; Paul T. Hamilton (Archives of Virology, 2014)

The diet of M yotis lucifugus across C anada: assessing foraging quality and diet variability - Elizabeth L. Clare; William O. C. Symondson; Hugh Broders; François Fabianek; Erin E. Fraser; Alistair MacKenzie; Andrew Boughen; Rachel Hamilton; Craig K. R. Willis; Felix Martinez‐Nuñez; Allyson K. Menzies; Kaleigh J. O. Norquay; et al. (Molecular Ecology, 2014)
Variation in prey resources influences the diet and behaviour of predators. When prey become limiting, predators may travel farther to find preferred food or adjust to existing local resources. When predators are habitat limited, local resource abundance impacts foraging success. We analysed the diet of Myotis lucifugus (little brown bats) from Nova Scotia (eastern Canada) to the Northwest Territories (north‐western Canada). This distribution includes extremes of season length and temperature and encompasses colonies on rural monoculture farms, and in urban and unmodified areas. We recognized nearly 600 distinct species of prey, of which ≈30% could be identified using reference sequence libraries. We found a higher than expected use of lepidopterans, which comprised a range of dietary richness from ≈35% early in the summer to ≈55% by late summer. Diptera were the second largest prey group consumed, representing ≈45% of dietary diversity early in the summer. We observed extreme local dietary variability and variation among seasons and years. Based on the species of insects that were consumed, we observed that two locations support prey species with extremely low pollution and acidification tolerances, suggesting that these are areas without environmental contamination. We conclude that there is significant local population variability in little brown bat diet that is likely driven by seasonal and geographical changes in insect diversity, and that this prey may be a good indicator of environment quality.

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Putting the brakes on a cycle: bottom‐up effects damp cycle amplitude - James R. Bell; Eric C. Burkness; Alice E. Milne; David W. Onstad; Mark Abrahamson; Krista L. Hamilton; William D. Hutchison (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 310–318 Abstract Pest population density oscillations have a profound effect on agroecosystem functioning, particularly when pests cycle with epidemic persistence. Here, we ask whether landscape‐level manipulations can be used to restrict the cycle amplitude of the European corn borer moth [ Ostrinia nubilalis (Hübner)], an economically important maize pest. We analysed time series from Minnesota (1963–2009) and Wisconsin (1964–2009) to quantify the extent of regime change in the US Corn Belt where rates of transgenic Bt maize adoption varied. The introduction of Bt maize explained cycle damping when the adoption of the crop was high (Minnesota); oscillations were damped but continued to persist when Bt maize was used less intensely (Wisconsin). We conclude that host plant quality is key to understanding both epidemic persistence and the success of intervention strategies. In particular, the dichotomy in maize management between states is thought to limit the spatial autocorrelation of O. nubilalis .

Physiological consequences of the supralittoral fringe: microhabitat temperature profiles and stress protein levels in the tropical periwinkle Cenchritis muricatus (Linneaus, 1758) - Michael L. Judge; Mark L. Botton; Mary G. Hamilton (Hydrobiologia, 2011)

Physiological responses of horseshoe crab (Limulus polyphemus) embryos to osmotic stress and a possible role for stress proteins (HSPs) - Morgan P. Greene; Mary G. Hamilton; Mark L. Botton (Marine Biology, 2011)

Using cattle for conservation objectives in a Scots pine Pinus sylvestris forest: results of two trials - Mark H. Hancock; Ron W. Summers; Andy Amphlett; Johanna Willi; Gary Servant; Alistair Hamilton (European Journal of Forest Research, 2010)

Evidence of a North Atlantic right whale calf ( Eubalaena glacialis ) born in northeastern U.S. waters - Melissa R. Patrician; Ingrid S. Biedron; H. Carter Esch; Frederick W. Wenzel; Lindsay A. Cooper; Philip K. Hamilton; Allison H. Glass; Mark F. Baumgartner (Marine Mammal Science, 2009)

Protective socking material for cultivated mussels: a potential non-disruptive deterrent to reduce losses to diving ducks - Mark Dionne; Jean-Sébastien Lauzon-Guay; Diana J. Hamilton; Myriam A. Barbeau (Aquaculture International, 2006)

Life‐history correlates of plant invasiveness at regional and continental scales - Mark A. Hamilton; Brad R. Murray; Marc W. Cadotte; Grant C. Hose; Andrew C. Baker; Carla J. Harris; Damian Licari (Ecology Letters, 2005)
We implemented cross‐species and independent‐contrasts multiple regression models to compare life‐history correlates of invasion success between regional and continental spatial scales among non‐native plants of eastern Australia. We focussed on three life‐history traits that represent major axes of variation in plant life history: specific leaf area (SLA), plant height and seed mass. After controlling for residence time and cross‐correlation with other life‐history traits, small seed mass was significantly and uniquely correlated with invasion success at continental and regional scales. High SLA was significantly and uniquely correlated with invasion success at the continental scale only. Plant height could not explain unique variation in invasion success at either spatial scale. Variation among spatial scales in the significance and strength of life‐history relationships with invasion success suggests that the search for predictive tools of invasion need not be fruitless, as long as predictive investigations are targeted at appropriate spatial scales.

Simulation of vertical position of buoyancy regulating Microcystis aeruginosa in a shallow eutrophic lake - Brett B. Wallace; Mark C. Bailey; David P. Hamilton (Aquatic Sciences, 2000)

DNA Sequence Evidence for Placement of the Ground Cuscus, Phalanger gymnotis, in the Tribe Phalangerini (Marsupialia: Phalangeridae) - Aaron T. Hamilton; Mark S. Springer (Journal of Mammalian Evolution, 1999)